EVALUATION OF TWO EMBRYO CRYOPRESERVATION METHODS IN LLAMA ON THE IN VIVO E IN VITRO EMBRYONIC SURVIVAL RATES - Vásquez E., Martha (2011)
The aim of the study was to evaluate in llama embryosthe effect of twocryopreservation methods on the in vivo and in vitro survival rate. Seventy three hatchedblastocysts were recovered by a non-surgical technique at day 6.5 after mating fromsuperstimulated llamas. Receptors were randomly allocated to a control group (n=14),vitrification (n=30) and slow freezing (n=29). On vitrification, embryos were exposed to avitrification solution (VS) containing 20% Glycerol + 20% Ethylene glycol + 0.5 M Sucrose+ 10% fetal calf serum (FCS) + 50 μg/ml gentamicin sulfate, and then plunged into liquidnitrogen in 0.25 ml straws. On the slow freezing, embryos were exposed to phosphatebuffer saline (PBS) with 1.5 M Ethylene glycol + 10% FCS + 50 μg/ml gentamicin sulfate,loaded in 0.25 ml straws, and cooled at a rate of 0.12 °C/min to 5 °C. Then, furthertemperature decrease at 5 °C /min rate, to -20 °C, for 5 min at the mouth of the nitrogentank; finally straws were plunged into liquid nitrogen. For thawing, two dilution solutionswere used composed of two sucrose concentrations: 0.5 M and 0.2 M for slow freezing,and 0.25 M and 0.12 M for vitrification. An in vivo evaluation was performed in allembryos of the control group and in 50% of the experimental groups by direct transferinto previously synchronized female recipients. Pregnancy diagnosis was carried out bytransrectal ultrasound evaluation at 20 and 30 days. Pregnancy was in 4/13, 2/12, and 0/11 in recipients from control, vitrification and slow freezing groups respectively, withoutsignificant difference. For the in vitro evaluation cryopreservated embryos were culturedin PBS + 20% FCS under atmosphere compose of 5% CO2, 20% O2, and 75% N2 at 39 °C for1 h, then reexpansion was recorded by morphological characteristics. Embryo reexpansionwas 75% (9/12) in vitrified embryos and 57.1% (4/7) in slow freezing embryos, and withoutsignificant difference. It was concluded that vitrification could be a suitable method forllama embryo cryopreservation.